ICA69 aggravates ferroptosis causing septic cardiac dysfunction via STING trafficking - Kong, Chang; Ni, Xuqing; Wang, Yixiu; Zhang, Anqi; Zhang, Yingying; Lin, Feihong; Li, Shan; Lv, Ya; Zhu, Jingwen; Yao, Xinyu; Dai, Qinxue; Mo, Yunchang; et al. (Cell death discovery, 2022)
Previous studies have demonstrated that cardiomyocyte apoptosis, ferroptosis, and inflammation participate in the progress of sepsis-induced cardiomyopathy (SIC). Although Islet cell autoantigen 69 (ICA69) is an imperative molecule that could regulate inflammation and immune response in numerous illnesses, its function in cardiovascular disease, particularly in SIC, is still elusive. We confirmed that LPS significantly enhanced the expression of ICA69 in wild-type (WT) mice, macrophages, and cardiomyocytes. The knockout of ICA69 in lipopolysaccharide(LPS)-induced mice markedly elevated survival ratio and heart function, while inhibiting cardiac muscle and serum inflammatory cytokines, reactive oxygen (ROS), and ferroptosis biomarkers. Mechanistically, increased expression of ICA69 triggered the production of STING, which further resulted in the production of intracellular lipid peroxidation, eventually triggering ferroptosis and heart injury. Intriguingly, ICA69 deficiency only reversed the ferroptotic marker levels, such as prostaglandin endoperoxide synthase 2 (PTGS2), malonaldehyde (MDA), 4-hydroxynonenal (4HNE), glutathione peroxidase 4 (GPX4), superoxide dismutase (SOD), iron and lipid ROS, but had no effects on the xCT-dependent manner. Additionally, greater ICA69 level was identified in septic patients peripheralblood mononuclear cells (PBMCs) than in normal control groups. Generally, we unveil that ICA69 deficiency can relieve inflammation and ferroptosis in LPS-induced murine hearts and macrophages, making targeting ICA69 in heart a potentially promising treatment method for SIC.